Development of mADM-collagen wound dressings for mimicking native skin architecture to enhance skin wound healing - Xiang Wang; Yujia Jiang; Xiaoqin Sun; Chongxia Yue; Zhengyong Li; Yao Wu (Collagen and Leather, 2024)
Abstract Acellular dermal matrix (ADM) is one of the most promising scaffold materials due to its ability to retain natural extracellular matrix structure. Micronized acellular dermal matrix (mADM) was prepared with no intact cell nuclei and preserved growth factors by High Hydrostatic Pressure (HHP) approach. And mADM-collagen wound dressings were developed with different proportion of type I collagen and recombinant humanized type III collagen. The porous structure of the mADM-collagen wound dressings made them a good candidate for preventing excessive fluid accumulation, while the collagens with gel-like texture combined with mADM powder to form pasty texture wound dressing, which preserving the moisture at the wound site. Moreover, the paste texture of the mADM-collagen wound dressing was easy to reshape to conform any wound shapes and body contours. Furthermore, the resulted mADM-collagen wound dressings showed good biocompatibility by supporting fibroblasts adhesion and proliferation in vitro. Subsequently, a murine model of full-thickness skin wounds was employed to assess its effects on wound healing. Notably, mADM-75% Col-I exhibited superior effects throughout the wound healing process, specifically it promoted neovascularization, skin appendage growth and new skin regeneration. This formulation closely mimicked the collagen ratio found in healthy skin, facilitating the favorable wound repair. These results indicated the superior performance of this mADM-collagen wound dressing providing an optimal environment for wound healing. Graphical Abstract